2021
DOI: 10.21014/acta_imeko.v10i2.1037
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Correction Method of Wind Speed for Efficiency Evaluation of Wind Turbines

Abstract: The performance of horizontal axis Wind Turbines (WTs) is strongly affected by the wind speed entering in their rotor. Generally, this quantity is not available, because the wind speed is measured on the nacelle behind the turbine rotor, providing a lower value. Therefore, two correction methods are usually employed, requiring two input quantities: the wind speed on the back of the turbine nacelle and the wind speed measured by a meteorological mast close to the turbines under analysis. However, the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…How to correct the wind speed has been an issue of great concern. For example, Malgaroli et al propose a nacelle wind speed correction for evaluating wind turbine performance by estimating the wind speed entering the wind rotor (Astolfi et al, 2021b;Carullo et al, 2021). In this paper, the nacelle wind speed compensation is mainly based on the aerodynamic and energy flow characteristics of the wind turbines (Dai et al, 2016b).…”
Section: Wind Speed Data Correctionmentioning
confidence: 99%
“…How to correct the wind speed has been an issue of great concern. For example, Malgaroli et al propose a nacelle wind speed correction for evaluating wind turbine performance by estimating the wind speed entering the wind rotor (Astolfi et al, 2021b;Carullo et al, 2021). In this paper, the nacelle wind speed compensation is mainly based on the aerodynamic and energy flow characteristics of the wind turbines (Dai et al, 2016b).…”
Section: Wind Speed Data Correctionmentioning
confidence: 99%
“…To set the hyperparameter λ, k-fold (with k = 10) cross-validation was performed [50]. Equation (7) was employed for simulating the output on the target data set D 2 , and the performance of the model, given the residuals between the model estimated and measurements (Equation ( 8)), was quantified through the most common metrics: MAE (Equation ( 9)), MAPE (Equation ( 10)), and RMSE (Equation ( 11)).…”
Section: Covariatementioning
confidence: 99%
“…The power curve analysis has the great advantage of simplicity, but the drawback is that it does not account for the fact that the power of a wind turbine has a multivariate dependence on the environmental conditions and working parameters [5]. Furthermore, the undisturbed wind flow is not measured directly: it is estimated through a nacelle transfer function based on downwind measurements collected behind the rotor span [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in [3], it was reported that in 2020, 28% of wind turbines installed in Europe were older than 15 years of age, with peaks in the order of 50% in Spain, Germany, and Denmark. This matter of fact motivates a recent deeper attention to the analysis and the interpretation of wind turbine performance, which is in general complicated because there are issues related with quantity and quality of nacelle anemometer data [4,5]. It is generally expected that the performance of whatever technical system declines with age [6,7] and the growing amount of aged operating wind turbines poses the issue of wind turbine performance analysis with a major urgency.…”
Section: Introductionmentioning
confidence: 99%